Penerapan COBIT-5 Domain DSS01 dan DSS05 Untuk Mengukur Kualitas Tata Kelola Sistem di KSPPS BMT Unit 068-Sampit - Anisa Agustina Melani; Angga Yogi Pratama; Muhammad Fajrin Anshari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Baitul Maal wa Tamwil (BMT) is an institution that supports the economic activities of low-income communities based on the Islamic sharia economic system. KSPPS BMT KUBE SEJAHTERA 068 Sampit was formed on January 12, 2006 with the legal entity Cooperative No. 07/Kep-BH/DK.PM/VIII/2006, and is a Sharia Savings and Loans Cooperative (KSPPS) which has approximately ten years of experience serving and partnering with the community. At KSPPS BMT-Sampit there is still no auditing system to monitor whether the existing technology is running well and efficiently, as well as to provide an assessment of the maturity level of information system technology, therefore the author uses the Cobit 5 framework for the audit system by focusing on 2 domains that the choices are DSS01 (manage operation) and DSS05 (manage security service) based on the results of calculations that have been done, the maturity level of information technology in KSPPS BMT-Sampit is at level 4 (Predictable processes) for DSS01, and based on level 4 (Predictable Processes) for DSS05